2017
DOI: 10.1021/acschembio.7b00180
|View full text |Cite
|
Sign up to set email alerts
|

A Macrocyclic Peptide Ligand Binds the Oncogenic MicroRNA-21 Precursor and Suppresses Dicer Processing

Abstract: MicroRNAs (miRNAs) help orchestrate cellular growth and survival through post-transcriptional mechanisms. The dysregulation of miRNA biogenesis can lead to cellular growth defects, chemotherapeutic resistance and plays a direct role in the development of many chronic diseases. Among these RNAs, miR-21 is consistently overexpressed in most human cancers leading to the down regulation of key tumor suppressing and pro-apoptotic factors; suggesting that inhibition of miR-21 biogenesis could reverse these negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 64 publications
(193 reference statements)
2
82
0
Order By: Relevance
“…1c). This observation is consistent with previous NMR studies on miR-21 precursor 33,34 , where mutations of the pre-element were made to quench the structural flexibility into a single conformational state 33 . When we carried out an NMR 13 C-1 H HSQC experiment that probes nonsolvent-exchangeable signals, surprisingly only 20 out of a total of 29 expected NMR resonances from preE-miR-21 were observed at room temperature ( Fig.…”
Section: The Pre-element Region Of Pre-mir-21 Samples Distinct Conforsupporting
confidence: 91%
“…1c). This observation is consistent with previous NMR studies on miR-21 precursor 33,34 , where mutations of the pre-element were made to quench the structural flexibility into a single conformational state 33 . When we carried out an NMR 13 C-1 H HSQC experiment that probes nonsolvent-exchangeable signals, surprisingly only 20 out of a total of 29 expected NMR resonances from preE-miR-21 were observed at room temperature ( Fig.…”
Section: The Pre-element Region Of Pre-mir-21 Samples Distinct Conforsupporting
confidence: 91%
“…Comparison of the top 20 NMR solutions confirms these as stable features of the molecule. NMR study of pre-miR-21 revealed weak signals corresponding to two tandem U-G/G-U pairs at the apical junction whereas the 14-nt apical loop is otherwise unstructured 31 .…”
Section: Discussionmentioning
confidence: 99%
“…1a). RNA secondary structure prediction programs tend to include base pairs in relatively long loops that are not necessarily stable 31,32 . We disregarded 1 or 2 base pairs that are separated from the hairpin stem on both strands.…”
Section: Survey Of Mir-precursor Apical Loop Lengthmentioning
confidence: 99%
See 2 more Smart Citations